The Value of Inclusion - Felder, Franziska (Journal of Philosophy of Education, 2018)
In recent years inclusion has become one of the most dominant values and objectives in education. However, there is still considerable disagreement concerning the theoretical concept of inclusion and its normative implications. This article suggests an understanding of inclusion that first differentiates analytically between societal and communal forms of inclusion, and second, situates the value of inclusion in the debate around recognition and freedom. Furthermore, it connects the discussion to some dilemmas and difficulties we might face in education. The overall approach and goal of the article is to contribute to the on-going debate on the nature and value of inclusion and inclusive education.